2015
DOI: 10.1097/pcc.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Screening Parents for Their Risk of Developing Psychological Symptoms After PICU

Abstract: All parents completed Impact of Event Scale-Revised and Hospital Anxiety and Depression Scale at 6 months. Of the 209 parents of 145 children recruited to the study, 78 (37%) were identified, on the basis of their Posttraumatic Adjustment Scale score at baseline, as being at risk of developing posttraumatic stress disorder, and randomized to the control or intervention condition. Follow-up data were provided by 157 of 209 parents (75%). Logistic regression analyses controlling for parent gender and child lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 22 publications
0
44
1
Order By: Relevance
“…These interventions were, however, provided at different time points, ranging from PICU admission (Melnyk et al, ) to within 7 days of discharge (Als et al . ) and 6 weeks after discharge (Gledhill et al, ) up to 2 months after discharge (Colville et al, ; Samuel et al, ) (Table ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These interventions were, however, provided at different time points, ranging from PICU admission (Melnyk et al, ) to within 7 days of discharge (Als et al . ) and 6 weeks after discharge (Gledhill et al, ) up to 2 months after discharge (Colville et al, ; Samuel et al, ) (Table ).…”
Section: Resultsmentioning
confidence: 98%
“…Studies varied in design, but all reported quantitative data (Table ). They included one full‐scale randomized controlled trial (RCT) (Melnyk et al, ), an exploratory RCT (Colville et al, ), a feasibility and pilot RCT (Als et al, ) and a feasibility study using a RCT design (Samuel et al, ). The remaining two studies used a non‐randomized design.…”
Section: Design and Methodsmentioning
confidence: 99%
“…29,30,33,34 Few centers reported having ICU follow-up clinics, an innovative multidisciplinary effort to address recovery from critical illness. 35 …”
Section: Discussionmentioning
confidence: 99%
“…PICU follow-up clinics have been suggested as one type of intervention to support parents most vulnerable to psychological distress after their child’s critical illness. However, a recent study reported that only a minority of parents were able or willing to participate in a PICU follow-up clinic appointment (22). Follow-up meetings or other interventions to support caregivers of children after OH-CA would need to be developed or adapted for this population, and tested for feasibility, acceptability and impact on family burden.…”
Section: Discussionmentioning
confidence: 99%